2013
DOI: 10.1248/bpb.b12-00880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnolol on Impairment of Learning and Memory Abilities Induced by Scopolamine in Mice

Abstract: Alzheimer's disease (AD), one of the most common forms of dementia, is primarily ascribed to the cholinergic deficits and neuronal dysfunction. Magnolol (Mag), a bioactivator extracted from Magnolia officinalis, has protective effects on cholinergic neurons, but the specific mechanism remains unknown. To further evaluate the therapeutic effects of Mag on the learning and memory impairment in a scopolamine (Scop)-induced mouse model, the passive avoidance and the Morris water maze tests, the measurement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…This finding is agrees with (Lopresti et al, 2014) who reported that depression is characterized by increased oxidative stress, as indicated by higher levels of MDA and 8-OHdG. (Li et al, 2013 and reported that MDA is one of the major metabolites induced by free radicals, and it can cause denaturation of biomembranes and mutation of DNA via increase level of 8-OHdG. Treatment with ATP caused an decline in the level of MDA and 8-OHdG as compared with reserpine group.…”
Section: Results:-supporting
confidence: 90%
“…This finding is agrees with (Lopresti et al, 2014) who reported that depression is characterized by increased oxidative stress, as indicated by higher levels of MDA and 8-OHdG. (Li et al, 2013 and reported that MDA is one of the major metabolites induced by free radicals, and it can cause denaturation of biomembranes and mutation of DNA via increase level of 8-OHdG. Treatment with ATP caused an decline in the level of MDA and 8-OHdG as compared with reserpine group.…”
Section: Results:-supporting
confidence: 90%
“…MDA is one of the major metabolites induced by free radicals, and it can cause denaturation of biomembranes and mutation of DNA. Moreover, MDA may decrease the activity of SOD (Li et al, 2013. This study found that cerebroprotein hydrolysate significantly decreased MDA levels and simultaneously increased the activity of SOD in the brain tissue of mice, indicating that cerebroprotein hydrolysate may significantly improve the scavenging of oxygen free radicals in brain tissue after SCOP-induced impairment of learning and memory.…”
Section: Discussionmentioning
confidence: 59%
“…The normal functioning of central cholinergic nerves is essential for learning and memory, and the impairment or decline of this function can affect the efficiency of learning and memory (Li et al, 2013). AChE is a specific hydrolase of ACh and one of the key substances in biological activity normally controlled by ACh.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 4-O-methylhonokiol, a novel compound isolated from Magnolia officinalis , prevents the development and progression of Alzheimer's disease by improving oxidative stress through a p38 MAPK-dependent pathway [25]. The beneficial effects of magnolol on learning and memory abilities were reported to be associated with superoxide dismutase (SOD) restoration in a scopolamine-induced mouse model [26]. However, how does magnolia extract modulate kidney inflammation and oxidative stress in obesity status is still unclear.…”
Section: Discussionmentioning
confidence: 99%